Atividade antinociceptiva e anti-inflamatória do extrato hexânico obtido das cascas do caule de Clusia nemorosa G. Mey. (Clusiaceae) - Ferro, Jamylle Nunes de Souza (2012)
Clusia nemorosa is distributed throughout Brazil and its extract is widely used in popular medicine to treat different diseases. Although the popular use of extract of C. nemorosa, the scientific reported on their pharmacological and phytochemical analysis are scarce. In the present study, we aimed to evaluate the antinociceptive and antiinflammatory effect of hexane extract of Clusia nemorosa-derived stem bark (EHC). To evaluate the antinociceptive effect of EHC classical models of the study of pain were used, such as the abdominal writhing test induced by acetic acid, formalin test and hot plate test. In order to evaluate anti-inflammatory effect of EHC, the model of paw edema induced by carrageenan were used. Rota-rod testing and toxicological analysis in vivo and in vitro were performed. Mices submitted to abdominal writhing test, was observed a significant reduction in nociceptive response induced by acetic acid, and these effects persisted for up to 2 h after treatment. Moreover, it is important emphasizing that the EHC did not induce changes in motor function of animals when the rota-rod test was performed. In order to investigate the possible mechanism of action of EHC, the animals were pretreated with naloxone (5mg/kg), yohimbine (1 mg/kg), atropine (5 mg/kg), metoclopramide (1 mg/kg), haloperidol (2 mg/kg) and L -NAME (20 mg/kg). Only when used metoclopramide, a serotoninergic and dopaminergic antagonist receptor, it was observed an inhibition of the antinociceptivo effect of EHC, suggesting that the serotoninergic pathway may be involved in the action of the EHC, as haloperidol, a dopaminergic antagonist did not reverse the antinociception of EHC. In addition, EHC did not induce changes in the nociceptive response of animals when assessed by the hot plate test, discarding the action in the central nervous system. Then, when the animals were treated with EHC and submitted to the formalin test, it was observed that only the second phase of this test was inhibited by the EHC, indicating inhibitory actions on pain of EHC from inflammatory origin. To evaluate possible toxic effects of EHC, animals were treated for 7 consecutive days. Then after treatment, were not observed changes in behavior, blood cellularity and cytotoxicity in vitro, which ruled out possible of toxic effects in these preliminary tests. Through analysis of gas chromatography coupled with mass spectrum, the major component present in the extract was identified, friedelin, who presented antinociceptive effects on pain and inflammation of neurogenic origin, as evidenced by the formalin test. Although this model of pain induced by formalin, it was observed that the antinociceptive effects friedelin were maintained when the EHC was administered orally. In addition, friedelin inhibited the paw edema induced by carrageenan. Lastly, in vitro assays, this triterpene did not affect cell viability as measured by MTT test. Together, our results support the popular use of this plant based on their anti-inflammatory and antinociceptive effects. In addition, we report the first time the presence of pentacyclic triterpenoid, friedelin on hexane extract of Clusia nemorosa-derived stem bark, triterpenoid which is possibly responsible for the pharmacological effects evaluated.